Genetic Divergence During Long‐term Isolation in Highly Diverse Populations of Tropical Trees Across the Eastern Arc Mountains of Tanzania. (14th August 2014) - Jump, Alistair S.; Carr, Martin; Ahrends, Antje; Marchant, Rob
Abstract The Eastern Arc Mountains are believed to support some of the oldest tropical forest in the world. The current distribution of this forest is highly fragmented due to a combination of long‐term effects of past changes in global climate and more recent deforestation. We sought to explore the hypothesized antiquity and long‐term isolation of the Eastern Arc montane forests based on an assessment of the geographical distribution and interspecies similarity of chloroplast DNA sequence variation in five forest trees. Data were used to investigate regional patterns of diversity and population structure based on intraspecific phylogenies, and results were interpreted against hypotheses on ecosystem age and connectivity. Regional diversity was high, with up to 22 chloroplast DNA haplotypes being recorded within a species across the sampled populations. Geographical concordance of genetic and geographic structure was weak to absent in all species and there was little similarity of genetic structure between species. Haplotype sharing between mountain blocks was extremely limited. The generally weak phylogeographical structure, in conjunction with high regional diversity and genetic uniqueness of individual mountain forests does not support the assumption of widespread genetic connectivity of the mountain forests, indicating instead a pattern of past isolation and ongoing diversification. Our findings substantially add to understanding patterns of diversity in this region and lend weight to calls to use more sophisticated biodiversity assessments when setting regional conservation and research funding priorities.